The relationship between diabetes mellitus and attention deficit hyperactivity disorder: A systematic review and meta-analysis - Ai, Yuan; Zhao, Jing; Liu, Hanmin; Li, Jiao; Zhu, Tingting (Frontiers in Pediatrics, 2022)
Background: This study aims to investigate the prevalence estimate of diabetes mellitus (DM) among people with attention deficit hyperactivity disorder (ADHD) as well as the prevalence of ADHD among those with DM. In addition, the impact of ADHD on glycemic control in patients with DM was also assessed using a systematic review and meta-analysis of currently available published data. Methods: The PubMed, Embase, Web of Science, and PsycInfo databases were searched for potential studies. Two reviewers independently selected studies according to the inclusion and exclusion criteria. All pooled analyses were conducted using the random-eﬀects models on Review Manager 5.3. Results: Seventeen observational studies were included. The pooled results showed an increase in the prevalence of DM among patients with ADHD versus those without ADHD (type 1 DM OR: 1.37 (95% CI: 1.17-1.61); type 2 DM OR: 2.05(95% CI: 1.37-3.07)). There was an overall 35% increase in the prevalence of ADHD among patients with type 1 DM (OR: 1.35 (95% CI: 1.08-1.73). Children with type 1 DM and ADHD had higher levels of hemoglobin A1c (standardized mean of differences: 0.67 (95% CI: 0.48-0.86)), and prevalence of hypoglycemic and ketoacidosis index compared with those without ADHD. Conclusion: Our study revealed the bidirectional associations between ADHD and DM. Patients with ADHD and type 1 DM comorbidities were more likely to have poorer diabetes control. More studies are needed to confirm this association and elucidate the underlying mechanism.